2012
DOI: 10.1021/jp209899m
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Bound Azido Groups Are Very Specific Water Sensors, Even in Hydrogen-Bonding Environments

Abstract: Covalently bound azido groups are found in many commercially available biomolecular precursors and substrates, and the NNN asymmetric stretching band of these groups is a strong infrared absorber that appears in a spectral region clear of other signals. In order to evaluate comprehensively the solvatochromism of the asymmetric azido NNN stretching band for site-specific use in biomolecular contexts, infrared spectra of the model compounds 5-azido,1-pentanoic acid and 3-(p-azidophenyl),1-propanoic acid were acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
100
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(112 citation statements)
references
References 46 publications
11
100
1
Order By: Relevance
“…The increased tolerance to incorporation of these probes at surface-exposed positions, along with their sensitivity to solvation, suggests that they are likely most useful as probes of surface hydration, as suggested previously based on solvent studies. [32,34] From this perspective, the uniquely large blueshift observed upon thermally induced folding of (CN)Phe186 is particularly interesting, as it suggests that solvation at the proteinwater interface is particularly strong, which is consistent with other studies indicating that proteins are hydrated by a layer of high-density water molecules. [51,52] This is also consistent with (CN)Phe186 being the only case where modification stabilizes the folded state of the protein.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…The increased tolerance to incorporation of these probes at surface-exposed positions, along with their sensitivity to solvation, suggests that they are likely most useful as probes of surface hydration, as suggested previously based on solvent studies. [32,34] From this perspective, the uniquely large blueshift observed upon thermally induced folding of (CN)Phe186 is particularly interesting, as it suggests that solvation at the proteinwater interface is particularly strong, which is consistent with other studies indicating that proteins are hydrated by a layer of high-density water molecules. [51,52] This is also consistent with (CN)Phe186 being the only case where modification stabilizes the folded state of the protein.…”
supporting
confidence: 86%
“…[21][22][23][24][25][26][27][28] The CN and N 3 probes have the advantage of being strong chromophores; however, unlike CÀD labels, CN and N 3 substituents are extrinsic probes that may introduce interactions that are not present in the native protein, and sensitivity to these artificial interactions may desensitize them to their native protein environment. Indeed, previous studies have indicated that both probes are predominantly sensitive to hydrogen bonding, [5,[29][30][31][32][33][34] interactions introduced by the probes themselves. Moreover, as extrinsic probes they might perturb the protein, a possibility exacerbated by the size of the N 3 group and by the H-bonding propensity of both CN and N 3 groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these methods, the spectroscopic methods especially fluorescence spectroscopy have been considered as a powerful alternative approach for the quantification of water content (Srivastava et al 2011;Wolfshorndl et al 2012;Luzinova et al 2012;Samadi-Maybodi et al 2012;Ooyama et al 2011). Various fluorescent dyes such as merocynanine dyes (Kumoi et al 1972), flavone derivatives (Cho et al 2005), luminescent nanospheres (Gao et al 2009), rhodamine 6G (Choi and Tse 1999), 10-allyl-acridine orange (Yang et al 2001), naphthalimide and its derivatives (Niu et al 2007) were introduced as fluorescence dye sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Thedata described in this work, corroborated by recent applications and advances in our understanding of its chromophoric properties [65 -68],p oint to ac lear superiority of Phe(p-CN)o ver Phe(p-NO 2 )a savibrational sensor.I nt his context, however, it is worth noting that recent publications have highlighted the overall, even more positive,p roperties of the azido-benzene IR label, including that occurring in Phe(p-N 3 )[ 69] [70]. As tudy on trichogin GA IV containing this latter residue is currently planned in our laboratory.…”
mentioning
confidence: 99%